DEFICIÊNCIA VISUAL: MAIS SENSÍVEL QUE UM OLHAR - Alessandra dos Santos Oliveira (Colloquium Humanarum, 2005)
The present work shows the experience of an intern group that carried out a project at the Philanthropic Association for Assintance to the Blind in Presidente Prudente (Associação Filantrópica de Proteção aos cegos de Presidente Prudente). It contains the application of the knowledge we acquired with the academic studies of Psichology in college and it intends to offer another service to the community. Our group used to gather at the office of the institution under the management of four students of Psichology supervised by a Professor. The study group consisted of twelve visually challenged people to use their special abilities and skills. They were always supported and given global attention. This extension project aimed to give several and diversified activities to the study group in order to stimulate other perception organs. Relevant and interesting themes were selected to be worked and they helped the study group to become aware of their citizenship. Social inclusion was specially literate and they belong to a class of low income. Effort was made to introduce the themes in an easy way so that they could understood.